Broadenıng the perspectıves : self-reflected benefıts from internatıonal student study tour / Syazliyati Ibrahim ... [et al.] - Ibrahim, Syazliyati; Zolhani, Nur Hidyati; Saad, Sharina (2019)
International mobility among students and lecturers are becoming more important in various universities. This criterion is getting to be more significant because it contributes to several factors such as university ranking, employers’ expectation and increased student’s marketability. In light of this, a mobility programme which involved a group of students to a foreign country was planned to expose them to the study tour experience. Upon completion of the programme, the students were asked to provide a self reflection by answering interview questions based on their experiences during the study tour. The findings generally showed that the students enjoyed the programme organised and their self reflections managed to record positive feedbacks such as strengthening of self confidence, increase in motivation level and improvement in English language presentations and speaking skills. In conclusion, international student study tour has a vast potential as an impactful programme which offers a myriad of benefits for the students.